Socialization of Improving Sales Quality for MSMEs in Semarang City - Ernawati, Fidyah Yuli; Irawati, Marsha Ayunita; Novandalina, Arini (MOVE: Journal of Community Service and Engagement, 2024)
The global recession will certainly weaken exports which are one of the sources of growth in Indonesia. Furthermore, weakening exports followed by shrinking foreign capital flows will weaken the rupiah exchange rate, especially as capital outflows have the potential to increase along with the increase in benchmark interest rates in developed countries. If we assume that the world will experience a recession, then the impact, both directly and indirectly, will hit the domestic economy, everywhere. Therefore, every country needs to prepare itself to face the threat of recession. Objective: To provide insight into improving the quality of sales for MSMEs in Semarang City and to provide outreach &; training on digitizing MSME sales in Semarang City. Implementation Method includes the following: (1 ) Planning and preparation (2) Implementation of training (3) Evaluation. core activities by delivering material on entrepreneurship digitalization and continued with the use of social media in implementing digitalization. The first material conveys the importance of digitalization for today's business, its role and stages of implementation. The second material discusses in detail what social media can be used, such as WhatsApp Business, Facebook Ads and other media that are currently being used, such as TikTok and Instagram. This activity ended with a discussion and questions and answers to strengthen the community's understanding and practice in utilizing digital media which has been explained. All Semarang City MSME Actor Training activities have been carried out smoothly and according to plan. The main aim of holding the training was to increase the knowledge and skills regarding the role of digitalization in entrepreneurship for the participants. especially for MSME business actors in Semarang City, it can be an opportunity for academics to carry out research and service. Optimizing understanding and practice in every community business is used to improve the marketing of its products and get better profits from these economic activities. The results can be used to focus on specific social media uses that are relevant to the target market.